Developing the Metacognitive Awareness of Grit Scale for a better understanding of learners of English as a foreign language - Wang, Mingzhe; Zhang, Lawrence Jun; Hamilton, Richard (Frontiers in Psychology, 2023)
The prominent impact of metacognition on learners’ academic achievement is widely discussed. Learners armed with appropriate metacognitive strategies should witness enhancement in learning performance. Similarly, the concept of grit is also valued as a crucial factor contributing to the improvement of academic achievement. Nevertheless, discussion of the relationship between metacognition and grit or their collective influence on other educational and psychological variables is limited, not to mention that an instrument measuring learners’ metacognitive awareness of grit is a desideratum. Hence, by incorporating the constructs of metacognition and grit, the present research developed a measurement scale to address this need, named the Metacognitive Awareness of Grit Scale (MCAGS). The MCAGS consists of four components and initially included 48 items. It was later distributed to 859 participants for the purpose of scale validation. Confirmatory factor analysis was applied to evaluate the scale’s validity and explore the factor-item relationship. A final model containing 17 items was retained. Implications and future directions were discussed.